Spatial Analysis and Sustainable-Strategic Environment Management at Baron Spring Catchment Area, Karst of Gunung Sewu, Yogyakarta - Hilary Reinhart; Andi Rifani (Jurnal Ilmu Lingkungan, 2019)
Gunung Sewu’s karstic aquifer characteristic of fracture-fissure water conduit leads to pollution problem in the water resources. One main source of water used is the Baron Spring. This study aims to analyze the water quality of the Baron Spring toward the land use in the catchment area and provide recommendations for spatial planning and water management in certain area. This research used spatial analysis of GIS and water quality was analyzed by Pollution Index. The results showed that the Baron Spring was in a mild contaminated state with amount of TSS was 97,1 mg/L, bicarbonate 96 mg/L, total coliform 210 MPN/100ml, and total oil and fat 2 mg/L which have exceeded the water source quality standards. Those results are related with the land use in the catchment area where settlement is dense in the upstream, also because of the distribution of settlement and sinkhole in the middle-part of catchment. In coping with the contamination and pollution several strategies are urged to be designed and implemented. Strategies comprised by two approaches, socio-cultural and spatial approach. Each of the approaches is linked and should not be separated. Management of catchment including stakeholder involvement and spatial planning are essential to be considered.